2018
DOI: 10.2298/sos1804487v
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, ceramic and technological properties of clays used in production of roofing tiles - principal component analysis

Abstract: This research describes a study of 11 selected samples of brick clays applied in roofing tile production, by using simultaneous thermal analysis. Additionally, the laboratorysized samples were prepared and fired (850-950 °C) and technological properties were determined. Mathematical analysis was applied to sum all the experimental results and help discriminate the samples by their behavior during firing. The samples, very similar according to mineralogical and chemical content, as well as granulometry tests, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The thermal analysis (Figure 3) showed that from room temperature to 225 °C, endothermic peaks in the DTA curve is accompanied with a 0.41% loss of mass in TG curve. This endothermic reaction is related to the escape of interlayer water of mineral phases [23]. The endothermic peaks at 528 °C is more accentuated and extended from 400 to 600 In this temperature range, the breakdown of kaolinite structure leads to the formation of a quasi-amorphous material of metakaolinite [5,24,25], according to equation ( 7):…”
Section: Differential Thermal Analysis (Dta) and Thermogrametry (Tg)mentioning
confidence: 99%
“…The thermal analysis (Figure 3) showed that from room temperature to 225 °C, endothermic peaks in the DTA curve is accompanied with a 0.41% loss of mass in TG curve. This endothermic reaction is related to the escape of interlayer water of mineral phases [23]. The endothermic peaks at 528 °C is more accentuated and extended from 400 to 600 In this temperature range, the breakdown of kaolinite structure leads to the formation of a quasi-amorphous material of metakaolinite [5,24,25], according to equation ( 7):…”
Section: Differential Thermal Analysis (Dta) and Thermogrametry (Tg)mentioning
confidence: 99%
“…The chosen firing temperatures were 950 °C,1000 °C, and 1050 °C. The slow-firing regime is followed, and the soaking time was 2 h (Vasić et al, 2018). The cooling was performed in natural conditions in a closed furnace.…”
Section: The Firing Of Laboratory Samplesmentioning
confidence: 99%
“…7. An initial weight loss of about 3 % is observed in the TGA curve, which is attributable to the evaporation of adsorbed water [29,30]. The departure of the structural water or the dehydroxylation of kaolin DD 1 occurs between 500 and 550 o C [31], accompanied by a loss of mass of the order of 3 %.…”
Section: Thermal Analysis Of Glazes Powdermentioning
confidence: 99%